2022
DOI: 10.1136/bmj-2021-067696
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 positivity in offspring and timing of mother-to-child transmission: living systematic review and meta-analysis

Abstract: Objectives To assess the rates of SARS-CoV-2 positivity in babies born to mothers with SARS-CoV-2 infection, the timing of mother-to-child transmission and perinatal outcomes, and factors associated with SARS-CoV-2 status in offspring. Design Living systematic review and meta-analysis. Data sources Major databases between 1 December 2019 and 3 August 2021. Study selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
139
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 46 publications
8
139
1
7
Order By: Relevance
“…It is reported in a living systematic review that SARS-CoV-2 infection was associated with increased risk of preterm birth [24,28], in line with our results that shown a nine-fold increased risk in symptomatic women.…”
Section: Obstetrical-neonatal Outcomessupporting
confidence: 93%
See 1 more Smart Citation
“…It is reported in a living systematic review that SARS-CoV-2 infection was associated with increased risk of preterm birth [24,28], in line with our results that shown a nine-fold increased risk in symptomatic women.…”
Section: Obstetrical-neonatal Outcomessupporting
confidence: 93%
“…Even though the percentage of complications was low, as per other studies (5.5-8.4%) [8,24], the risk of an adverse outcome in the prepartum and/or postpartum period increased in symptomatic patients, especially those with severe disease. In addition, as other studies have shown [21,28,34,37], the maternal mortality rate attributed to COVID-19 was higher than our study (~1.6% vs. 0.8%). Our study identified no association between maternal background disease and the manifestation of COVID-19 symptoms.…”
Section: Obstetrical-neonatal Outcomessupporting
confidence: 65%
“…Since the COVID-19 outbreak, the impact of SARS-CoV-2 on the placenta and its potential for vertical transmission has been raised concerns [19] . A recent meta-analysis published in BMJ confirmed vertical transmission of SARS-CoV-2, and the severity of maternal COVID-19 appears to correlate with infant SARS-CoV-2 positive [20] . Several previous studies have examined the hearing screening outcomes of newborns whose mothers tested positive for SARS-CoV-2 during pregnancy, revealing an increased risk of HL in these newborns [7] , [21] .…”
Section: Introductionmentioning
confidence: 91%
“…Although intrauterine transmission is possible from a pathophysiological standpoint, actual in-utero infections appear to be rare, estimated at 2% [6]. Infection outcomes during pregnancy were divided according to the trimester in which the mother was infected: first, second and third trimester.…”
Section: Introductionmentioning
confidence: 99%